2022
DOI: 10.1371/journal.pone.0270484
|View full text |Cite
|
Sign up to set email alerts
|

The ability of energy recovery in professional soccer players is increased by individualized low-intensity exercise

Abstract: The aim of this study was to investigate whether individualized low-intensity exercise (ILIE) within the recovery domain before lactate threshold 1 (LT 1) improves energetic recovery and general endurance capacity in professional soccer players. Twenty-four professional soccer players (age: 24.53 ± 4.85 years, height: 180 ± 6.30 cm, body mass: 75.86 ± 8.01 kg, body fat: 12.19 ± 2.69%) participated in the study (n = 24). The 1-h ILIE intervention involved 27 jogging sessions spanning nine weeks and jogging spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 56 publications
(109 reference statements)
0
21
0
Order By: Relevance
“…This anaplerotic mechanism is necessary for gluconeogenesis, lipogenesis, and ATP re-synthesis from lactate during low-intensity exercise in well-trained athletes [ 5 , 10 , 21 , 40 ]. FATox activates crucial enzymes and hormonal responses of gluconeogenesis such as pyruvate kinase, PC, phosphoenolpyruvate carboxykinase, epinephrine, glucagon, cortisol, and other related regulators such as cyclic adenosine monophosphate and intracellular Ca + handling [ 10 , 16 , 17 ]. In these regards, comparisons of CHOox between both groups and negative correlation and regression analyses between La − and FATox support these mechanisms and the differences in mitochondrial function between both groups [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This anaplerotic mechanism is necessary for gluconeogenesis, lipogenesis, and ATP re-synthesis from lactate during low-intensity exercise in well-trained athletes [ 5 , 10 , 21 , 40 ]. FATox activates crucial enzymes and hormonal responses of gluconeogenesis such as pyruvate kinase, PC, phosphoenolpyruvate carboxykinase, epinephrine, glucagon, cortisol, and other related regulators such as cyclic adenosine monophosphate and intracellular Ca + handling [ 10 , 16 , 17 ]. In these regards, comparisons of CHOox between both groups and negative correlation and regression analyses between La − and FATox support these mechanisms and the differences in mitochondrial function between both groups [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that high aerobic conditioning comprising an aerobic base such as energy recovery is associated with improved sports performance, cardiometabolic fitness, efficient fat and carbohydrate utilization, and metabolic flexibility in adults and elite athletes. These improvements comprise decreased La − , CHOox, and increased FATox [ 5 , 10 , 13 , 16 , 17 , 21 , 49 ]. Performance-related jogging/running speeds were higher at all steps, and more steps were performed in A than in GP, who utilized higher FATox and lower carbohydrates during GIET.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations